2020
DOI: 10.1302/1863-2548.14.200010
|View full text |Cite
|
Sign up to set email alerts
|

The metaphyseal fossa surrounding the epiphyseal tubercle is larger in hips with moderate and severe slipped capital femoral epiphysis than normal hips

Abstract: Purpose To compare the 3D morphology of the metaphyseal fossa among mild, moderate and severe stable slipped capital femoral epiphysis (SCFE) and normal hips. Methods We identified pelvic CT of 51 patients (55% male; mean 12.7 years (sd 1.9; 8-15)) with stable SCFE. In all, 16 of 51 hips (31%) had mild, 14 (27%) moderate and 21 (41%) severe SCFE. A total of 80 patients (50% male; mean age 11.5 years (sd 2.3; 8 to 15)) with normal hips who underwent pelvic CT due to abdominal pain made up the control cohort. CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
2
8
2
Order By: Relevance
“…However, a previous study showed that the metaphyseal fossa is larger in hips with moderate and severe SCFE than normal hips. 19 The discrepancy of our findings may be due to the proportion of severe (41%) and moderate (27%) SCFE in the previous study while our cohort had too few severe cases. Similarly, we saw smaller fossa length, compared to the contralateral uninvolved hip, in acute SCFE cases while there was no side-to-side difference in chronic SCFE cases.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…However, a previous study showed that the metaphyseal fossa is larger in hips with moderate and severe SCFE than normal hips. 19 The discrepancy of our findings may be due to the proportion of severe (41%) and moderate (27%) SCFE in the previous study while our cohort had too few severe cases. Similarly, we saw smaller fossa length, compared to the contralateral uninvolved hip, in acute SCFE cases while there was no side-to-side difference in chronic SCFE cases.…”
Section: Discussioncontrasting
confidence: 72%
“…10,14,18 Several previous studies have described SCFE as a rotational deformity and highlighted the role of the epiphyseal tubercle in the pathogenesis of SCFE. 11,[15][16][17]19 Furthermore, research utilizing computed tomography (CT) has reported that the epiphyseal tubercle is smaller, while the metaphyseal fossa and the peripheral cupping are larger in hips with severe SCFE compared to healthy control hips. 13,19 Nevertheless, CT examinations are limited to the assessment of the bony margins of the epiphysis and metaphysis and are not the ideal modality for investigating the changes to the growth plate, which is a cartilaginous structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the limbs of the typically developing (TD) child grow, there is a programmed modelling of the long bones with systematic changes in length, width, and version (Herring and Tachdjian, 2020). Atypical development, such as children suffering from cerebral palsy or slipped capital femoral epiphysis (SCFE), can lead to delayed or altered skeletal modelling with consequent effects on hip stability, gait pattern and limb alignment (Gage et al, 2009;Hosseinzadeh et al, 2020). Understanding morphological variation in the typically developed skeleton is important to diagnose and treat morphological variations and pathology.…”
Section: Why We Need Bone Measurement and Modelsmentioning
confidence: 99%
“…It is conceivable that deficiencies in the development of the subchondral bone plate and mammillary processes may result in weakening of the interface and could contribute to conditions such as slipped capital femoral epiphysis (SCFE). SCFE is characterized by a non-traumatic displacement of the femoral metaphysis with respect to the capital femoral epiphysis through failure of the physis and is believed to have a multifactorial etiology involving biomechanical, biochemical, endocrine and developmental factors [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%